2012
DOI: 10.1371/journal.pone.0030840
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Inhibits Epithelial-to-Mesenchymal Transition in Endometrial Cancer

Abstract: BackgroundEvery year approximately 74,000 women die of endometrial cancer, mainly due to recurrent or metastatic disease. The presence of tumor infiltrating lymphocytes (TILs) as well as progesterone receptor (PR) positivity has been correlated with improved prognosis. This study describes two mechanisms by which progesterone inhibits metastatic spread of endometrial cancer: by stimulating T-cell infiltration and by inhibiting epithelial-to-mesenchymal cell transition (EMT).Methodology and Principal FindingsPa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 57 publications
2
53
1
2
Order By: Relevance
“…Finally, activation of the IL6 signaling cascade results in the de novo generation of CSCs through induction of EMT (38). The latter is also in agreement with our previous study, where increased expression levels of IL6 and STAT3 were detected in endometrial tumors displaying EMT features (39). Our RT-qPCR analysis of several EMT-related genes in endometrial cancer cell lines identified differential expression between the ALDH hi and ALDH lo subpopulations of the HEC1A cell line only in the case of TWIST1 and TWIST2 ( Supplementary Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, activation of the IL6 signaling cascade results in the de novo generation of CSCs through induction of EMT (38). The latter is also in agreement with our previous study, where increased expression levels of IL6 and STAT3 were detected in endometrial tumors displaying EMT features (39). Our RT-qPCR analysis of several EMT-related genes in endometrial cancer cell lines identified differential expression between the ALDH hi and ALDH lo subpopulations of the HEC1A cell line only in the case of TWIST1 and TWIST2 ( Supplementary Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, progesterone contributes to the dynamic modification of the endometrial epithelium during the menstrual cycle by inhibiting Wnt/beta-catenin signaling, which is also required for maintaining endometrial homeostasis and for contrasting progression toward hyperplasia and carcinogenesis [29,30]. We found that AA induced an increase in progesterone levels and prevented the nuclear accumulation of beta-catenin in NCI-H295R cells.…”
Section: Discussionmentioning
confidence: 86%
“…The loss of E-cadherin expression in EEC is associated not only with the CDH1 gene mutations [17], but also with CDH1 promoter hypermethylation [18] and dysregulation of the proteins, which normally inhibit the E-cadherin expression. The loss of E-cadherin expression is a poor prognostic factor for the patients with EEC [10], because this loss is associated with the phenomenon of epithelial-mesenchymal transformation, which includes the loss of apical-basal polarity of the cancer cells, the increasing of the mesenchymal integrins synthesis by these cells, the migration of the tumor cells into the adjacent tissues and also the tumor metastasis [19].…”
Section: Resultsmentioning
confidence: 99%